Analysis of verbal diadochokinesis in normal speech using the diadochokinetic rate analysis program - Cheng-Chieh Yang; Yuh-Mei Chung; Lin-Yang Chi; Hsiu-Hsien Chen; Yu-Tsai Wang (Elsevier, 2011)
Background/purpose: The purposes of this study were to report the suitability, alternate-forms reliability, and the concurrent validity of the analysis of diadochokinesis (DDK) samples in normal speech using the Diadochokinetic Rate Analysis (DRA) program. Methods: Fifteen healthy participants were recorded as they repeated various syllables as quickly and steadily as possible. When the lowest peak intensity during consonant-vowel syllables is lower than the highest peak intensity during intersyllable pauses, the DRA output is incorrect and the DDK sample is defined as nonexecutable. The executable DDK samples were hand measured and executed by the DRA program to generate outputs at different thresholds. Analyses were based on the percentage of nonexecutable DDK samples and the comparisons of the results between repeated analyses at different thresholds and between automatic and manual measuring methods. Results: One-ninth of the DDK samples could not be accurately executed. When the protocol could be accurately executed, the reliability at different thresholds and the validity between different measuring methods were both satisfactory. Conclusion: Although inadvertent articulatory breakdown or the incoordination of intrasyllabic movements were major limiting factors to the suitability, the alternate-forms reliability and concurrent validity of the analysis of DDK in adults with normal speech using the DRA program were both satisfactory if the DDK train was executable by DRA.